Discourse patterns in primary mathematics classes - Bacungan, Amelia Ordona 1948-
This study described and analyzed the patterns and discourse in primary Mathematics classes using a tri-partite dimensional model which consists of Sinclair and Coulthard's linguistic analysis, Krashen's comprehensibility strategies and Henderson's concept venture moves.